The nature of recognition in tefl teachers’ lives (2011)
This article aims at sharing a vital issue that emerged from the findings of a qualitative research study into collective responses of teachers of English as a foreign language to an extended change process in their Mexican university context from 1989 to 2003. The data generation process employed was comprised of semi-structured interviews as well as the concurrent analysis of the data, based on aspects of grounded theory. The results of this inquiry demonstrated features of the complexity paradigm of educational change. In particular, how teachers’ receptivity to change was strongly influenced by the teachers’ transforming construal of their professional identities owing to the growing recognition they acquired in their context.En este artículo se aborda una problemática vital, descubierta en los resultados de una investigación cualitativa. Dicha investigación se enfocó en las respuestas colectivas de maestros de inglés como lengua extranjera, en el contexto de una universidad mexicana, entre 1989 y 2003, hacia un proceso de cambio. En la recolección de datos se emplearon entrevistas semiestructuradas, así como el análisis concurrente de los datos con base en la teoría fundamentada. Los resultados mostraron características del paradigma de la complejidad del cambio educacional. Específicamente, se observó que la receptividad hacia el cambio fue influenciada fuertemente por la construcción positiva de identidad profesional propia de los maestros, cimentada en el desarrollo de su reconocimiento como profesionales dentro de su contexto.